Isolation and molecular characterization of a novel cytopathogenic paramyxovirus from tree shrews - Tidona, Christian; Kurz, Hans Wolfgang; Gelderblom, Hans R.; Darai, Gholamreza (Virology, 1999)
A cytopathic infectious agent was isolated from the kidneys of an apparently healthy tree shrew (Tupaia belangeri) that had been captured in the area around Bangkok. The infectivity was propagated in Tupaia fibroblast and kidney cell cultures. Paramyxovirus-like pleomorphic enveloped particles and helical nucleocapsids were observed by electron microscopy and accordingly the infectious agent was termed Tupaia paramyxovirus (TPMV). However, no serological cross-reactions were detected between TPMV and known paramyxoviruses. For the molecular characterization of TPMV an experimental strategy that allows the random-primed synthesis of relatively large cDNA molecules from viral genomic RNA was applied. Nucleotide sequence analysis of a TPMV-specific cDNA fragment (1544 bp) revealed two nonoverlapping partial open reading frames corresponding to paramyxoviral N and P transcription units. Using modified rapid amplification of cDNA ends techniques, a substantial contiguous portion of the viral genome (4065 nt) was elucidated including the complete N and P/V/C genes. The coding strategy of TPMV as well as significant amino acid sequence homologies clearly indicates an evolutionary relationship between TPMV and members of the genus Morbillivirus. Highest homologies were detected between TPMV and Hendra virus (equine morbillivirus), which recently emerged in Australia, causing outbreaks of fatal respiratory and neurological disease in horses and humans.
Gesehen am 19.03.2021